Text game - Cann, Kate. (Edinburgh : Stoke Books, 2012)
Mel becomes suspicious of her new boyfriend after she receives weird texts.
3.0
Young Adult.
Young Adult
Keywords: Man-woman relationships -- Juvenile fiction; Text messages (Cell phone systems) -- Juvenile fiction; Man-woman relationships -- Fiction; Text messages (Cell phone systems) -- Fiction; Man-woman relationship -- Fiction; Text messages (Cell phone systems) -- Fiction